The Flow Characteristic Of Simulation For Newly Developed Disposable Inhaler Spacer Geometry - Nur Dinie Izzati Abdul Rahman; Mohammad, Sofian (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Pressurized metered-dose inhalers (pMDIs) are widely used for airway disease treatment, but incorrect usage reduces their efficiency, with much of the drug depositing in the oropharynx. Spacer devices were developed to slow aerosol particles and improve lung deposition. This study compares four spacer designs using Computational Fluid Dynamics (CFD) in SolidWorks 2024, focusing on outlet velocity and pressure. Results showed that WT-Model 4 provided the most efficient and uniform airflow distribution, with velocities ranging from 0.361–1.874 m/s (average 1.628 m/s) and stable outlet pressures around 101324.84 Pa, indicating improved aerodynamic performance and drug delivery potential.